Distribuição espacial da biomassa fitoplanctônica e sua relação com os sais nutrientes, no sistema estuarino de barra das jangadas (Pernambuco – Brasil) - Noriega, Carlos Delgado (2020)
The Barra das Jangadas estuarine system is located at the Jaboatão dos Guararapes Town, 20km south of Recife city, and it is formed by the Pirapama and Jaboatão Rivers. The area main economical activity is the artisanal fisheries. The objective of this paper is to evaluate the environmental quality through the phytoplankton biomass spatial distribution and the hydrological parameters. Surface samples (dissolved oxygen, BOD, temperature, salinity, nutrients, chlorophyll-a and suspended material) were collected in 15 fixed stations with a Nansen bottle during diurnal low tide. The phytoplankton biomass presented a maximum of 111.13mg.m3 indicating an euthrophic condition. Nutrients weren’t limitant to the phytoplankton development, presenting a non conservative pattern. Ammonium, phosphate and silicate influenced the primary biomass, being removed from nearly all estuary. The high N:P ratio indicated anthropic impacts as domestic and/or industrial pollution, and the biological uptake or sedimentation of the phosphate compounds. The salinity pattern showed a vertical homogenous estuary. According to Principal Component Analysis the phytoplankton biomass showed a high direct correlation with the suspended material, while the dissolved oxygen, saturation tax, salinity, pH and transparence presented direct correlation among them and were inversely correlated to the nutrients and BOD.